TOXIC ACTIVITIES OF HEXANE EXTRACT AND COLUMN CHROMATOGRAPHY FRACTIONS OF RODENT TUBER PLANT (Typhonium flagelliforme Lodd.) ON Artemia salina - Nesti F. Sianipar; Wilmar Maarisit; Alice Valencia (Indonesian Agency for Agricultural Research and Development, 2013)
Rodent tuber (Typhonium flagelliforme Lodd.) is a medicinal plant particularly found in Java. The plant is used as an ingredient for conventional cancer treatment. The aim of this study was to determine the toxic activities of crude extracts and column chromatography fractions of rodent tuber on Artemia salina larvae. Rodent tuber plant was obtained from the Indonesian Spice and Medicinal Crops Research Institute in Bogor, West Java. The experiment was conducted in the Biology Laboratory of Universitas Pelita Harapan, Tangerang, Banten. Leaves and petioles of the plant were macerated with acetone and the filtrates were evaporated (40°C) to obtain crude extracts. The crude extracts were partitioned with ethyl acetate, followed with hexane, chloroform and butanol. Toxicity test of the extracts was performed using the Brine Shrimp Lethality Test (BSLT) method on A. salina larvae. Extract showing the most toxic was fractioned using column chromatography and then tested on the larvae. The experiment was designed in a completely randomized factorial, four replicates for crude extracts and two replicates for the fractions. Treatments were different types of extracts (hexane, chloroform and butanol) at various concentrations (500, 1,000 and 1,500 μg ml-1 of 5% Tween solution). Fractions of the column chromatography used were taken from the column number 1, 3 and 10, and tested their toxicities at 200, 400, 600, 800 and 1,000 μg ml-1 of 5% Tween solution. Parameters observed were the death of A. salina expressed as LC50. The study showed that hexane extract of the petioles had the most toxic to A. salina (LC50 = 762.08 μg ml-1). Fraction number 10 showed the highest toxic (LC50 = 381.07 μg ml-1), whereas the lowest was fraction number 3 (LC50 = 653.13 μg ml-1). The study indicates that rodent tuber plant from Bogor is toxic to A. salina and further test for its cytotoxic activity is justified.